Strukturalisme dan Revitalisasi Applied Linguistics - Wahyu Hanafi Putra (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: The structuralism by using behavioristik concept in language learning. In behavioristik approach, learning is the result of interaction between stimulus and response. Behavioristik concept also touches the area of an applied linguistics called learning Arabic. The one of behavioristik aspect in learning Arabic is such as speech and habit, language is a system of sign (signifie and signifiant, and also gramatical language based of generality.Keywords: Structuralism, Behavioristik, Learning Arabic